Environmental effects on long-range outcrossing rates in maize - Kawashima, Shigeto; Nozaki, Haruhiko; Hamazaki, Takahiro; Sakata, Satoshi; Hama, Takehide; Matsuo, Kazuhito; Nagasawa, Arihiro (Agriculture, ecosystems & environment, 2011)
[Display omitted] ► The outcrossing rate did not reach zero even at points 800 m distant from pollen source. ► The outcrossing rate at long distances continued to decrease in a very gradual manner. ► The reduction of outcrossing rate with distance is smaller under higher wind speed. ► The distribution of outcrossing rates is affected strongly with the climatic conditions. With the aims of clarifying the effects of genetically modified crops on the environment, along with investigating the coexistence rules for genetically modified (GM) crops and existing non-GM crops, we carried out outcrossing experiments with maize. To clarify the actual conditions and characteristics of long-range outcrossing rates in particular, the present research conducted over the 3-year period of 2006–2008 involved performing outcrossing experiments using large-scale plots and obtaining data on meteorological observations, outcrossing rates, and pollen observations. These experiments significantly expanded the scale of the test plots from previous work on this subject, with measurements of outcrossing rates at long distances and investigations of the effect of meteorological elements and pollen count. The outcrossing rate was estimated as the percentage of yellow kernels produced among the white kernels due to the pollination of the recipient female flowers of the white-kernel cultivar by the donor flower pollen of the yellow-kernel cultivar. The following was clarified from these results. (1) Precipitation from the date of flowering to the day before the peak pollen dispersion period suppressed the amounts of pollen dispersed during the peak period, and was one of the factors that determined the pattern of pollen dispersal. (2) Outcrossing did not occur in a spatially homogeneous manner, and the distribution produced isolated islands of high outcrossing rate. Even in locations that were several hundred meters from the donor, outcrossing did not occur in a spatially homogeneous manner. (3) The outcrossing rate decreased exponentially as a function of distance from the donor field, but did not reach zero even at points 800 m distant, nor did the values become uniform. They continued to decrease in an extremely gradual manner. (4) In the relationship between outcrossing rate and distance from the donor, the higher the mean wind speed, the smaller the reduction of outcrossing rate with distance. In addition, the greater the amount of solar radiation, the larger the reduction of outcrossing rate with distance.